Digital Game-Based Language Learning in EFL Context: An Analysis of Genshin Impact in Indonesian Classrooms - Astuti, Winda Astrid Puji; Oktavianti, Ikmi Nur (Ahmad Dahlan Journal of English Studies, 2026)
Recent technological advances have transformed approaches to language learning, with Digital Game-Based Language Learning emerging as a promising field of study. While many studies have examined quiz-based or language-learning-specific applications, limited research has explored the potential of popular open-world games such as Genshin Impact for structured EFL learning. This study aims to (1) identify English language skills that can be developed through Genshin Impact, and (2) analyze the pedagogical applicability of game elements within a DGBLL framework. A qualitative, descriptive-analytic design was employed, involving classroom observations, interviews with students and teachers, and questionnaire data collection. The study was conducted at a public senior high school in Berau with 10th grade students and English teachers as participants. Data were analyzed through content analysis, including reduction, display, and interpretation of emerging themes. The analysis revealed that Genshin Impact supports the development of vocabulary enrichment, reading comprehension, listening comprehension, and discourse/pragmatic skills. Beyond language outcomes, the game fosters motivation, engagement, and authentic exposure to English. Teachers and students perceived both opportunities and challenges in integrating the game into formal classroom contexts. The findings contribute to expanding the scope of Digital Game-Based Language Learning research by highlighting the pedagogical potential of a widely played entertainment game. For practice, the study provides insights for EFL teachers and curriculum developers in Indonesia, particularly in rural and remote regions, to harness students’ gaming interests for language learning.